Silent Scars: The Psychological toll of infertility on women of reproductive age - Jabeen, Musarrat; Saba, Naseem; Zuhra, Hina; Rauf, Isma; Samreen Hamid, Beenish; Khan, Fareeha (Journal of Neonatal Surgery, 2025)
Background:Infertility is a life-changing condition that goes beyond physical incapacity to conceive and usually leaves a tremendous emotional burden on women. In cultures where motherhood is directly associated with social identity and marital stability, infertile women can be subjected to chronic psychological trauma, social stigma and isolation. Irrespective of this, the psychological aspects of infertility are under-researched in standard clinical practice. Objective:To assess the frequency of psychological distress and to identify associated social and clinical factors among infertile women of reproductive age. Methodology:The study was a descriptive cross-sectional study that was cocnducted between January 2023 and January 2024 in District Women Hospital MTI Dera Ismail Khan and Liquid Memorial Hospital Kohat. The sample was recruited using consecutive sampling of 81 women aged 1845 years with clinical diagnosis of infertility. The psychological condition was assessed through proven screening instruments of depression, anxiety, perceived stress, sleep disturbance, and self-esteem. Data analysis was through descriptive and inferential statistics. Results:Depressive symptoms of moderate to severe severity were noted in 50.6, anxiety in 56.8, and high perceived stress in 60.5 of the participants. Fifty-four point three percent of the women had reported sleep disturbance, and 46.9 percent exhibited low self-esteem. Women who had not conceived in more than five years as well as those who had social stigma and domestic conflict and poor social support had a greater psychological morbidity. Conclusion:Infertility is associated with a substantial psychological burden that intensifies with prolonged disease duration and unfavorable social environments. Routine mental health screening should be incorporated into infertility care services